Roll spin: media latihan pukulan forehand spin dalam tenis meja - Royana, Ibnu Fatkhu; Zhannisa, Utvi Hinda; Herlambang, Tubagus (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
This study aims to create a development of forehand spin training media to determine the effectiveness level of forehand spin training media development in table tennis. The problem in this study was the absence of training media focused on increasing forehand spin and the unknown of the effectiveness of developing forehand spin training media named roll spin. The research method used was development research. The development procedure used included several stages, namely: 1) Analyzing the product being developed, 2) Developing the initial product, 3) Validating the expert, 4) Field testing, 5) Product revision, 6) Field testing. The instruments used were questionnaires and interviews. The results showed that the development of roll spin media proved effective as a medium of training to improve forehand spin of table tennis at UPGRIS Table Tennis club with the results of the effectiveness of media experts with a mean score of 4.5 in the "very good" category, the results of the material experts with a mean score of 4.7 in the "very good" category, and the results of the trial with the participants of UPGRIS Table Tennis club with an average number of 3.84 in the "good" category.